Determinantes de la demanda de productos agrícolas estratégicos de México con ventajas comparativas reveladas en EE. UU. y Canadá, 1990-2019 - López Villaseñor, Alejandro Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The thesis analyzes the determinants of the demand for agricultural products SAGARPA, with comparative advantages revealed in the US. and Canada. According to the theory of demand, the variables that determined are: price, consumer income, consumer and their preferences, and product of the competition. To be quantified, a registry was prepared by reviewing the literature, which concentrated seventy-one factors. They were depurated and included with their variable, leaving: price, exchange rate, gross domestic product, domestic spending on food, historical purchases, purchase of other agricultural products, imports and the price of the competition. The vector error correction model was applied to evaluate the thirteen products with VCR in the US. and six in Canada. The model explained between 75 % and 99.80 % of the demands: the variable "consumer and their preferences" was significant in 17 models, "competitive product" in 9, "price" in 8 and "consumer income" in 8. The determining factors were: price in 11 models, other agricultural imports in 10, competitor's price in 8, domestic spending on food in 7, gross domestic product in 6, competitor's imports in 6 and exchange rate in 4. It is concluded that the fidelity on the part of the demand, explained by the commercial, social and cultural relations mainly determines its consumption; the price of Mexico is a determining factor, however, it is observed that the price of the competition exerts pressure to obtain participation in the North American market.

La tesis analiza los determinantes de la demanda de productos agrícolas SAGARPA, con ventajas comparativas reveladas en EE. U.U. y Canadá. Según la teoría de la demanda, las variables que influyen, son: precio, ingreso del consumidor, consumidor y sus preferencias, y producto de la competencia. Para cuantificarse, se elaboró un registro mediante la revisión de la literatura, que concentró setenta y un factores. Se depuraron e incluyeron con su variable, quedando: precio, tipo de cambio, producto interno bruto, gasto doméstico en alimento, compras históricas, compra de otros productos agrícolas, importaciones y precio de la competencia. Se aplicó el modelo vector autorregresivo con corrector de errores para evaluar los trece productos con VCR en EE. U.U. y seis en Canadá. El modelo entre el 75 % y 99.80 % de las demandas: la variable “consumidor y sus preferencias” fue significativo en 17 modelos, “producto de la competencia” en 9, “precio” en 8 e “ingreso del consumidor” en 8. Los factores determinantes fueron: precio en 11 modelos, otras importaciones agrícolas en 10, precio de la competencia en 8, gasto doméstico en alimentación en 7, producto interno bruto en 6, importaciones de la competencia en 6 y tipo de cambio en 4. Se concluye que la fidelidad por parte de la demanda, explicada por las relaciones comerciales, sociales y culturales determinan principalmente su consumo; el precio de México es un factor determinante, sin embargo, se observa que el precio de la competencia ejerce presión para conseguir participación en el mercado de Norteamérica.
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6783; info:eu-repo/classification/cti/5; FCCA-D-2022-0041; Demanda de productos agrícolas; Ventajas comparativas reveladas; Administración estratégica